2017
DOI: 10.1007/s10796-017-9789-4
|View full text |Cite
|
Sign up to set email alerts
|

Institutional vs. Non-institutional use of Social Media during Emergency Response: A Case of Twitter in 2014 Australian Bush Fire

Abstract: Social media plays a significant role in rapid propagation of information when disasters occur. Among the four phases of disaster management life cycle: prevention, preparedness, response, and recovery, this paper focuses on the use of social media during the response phase. It empirically examines the use of microblogging platforms by Emergency Response Organisations (EROs) during extreme natural events, and distinguishes the use of Twitter by EROs from digital volunteers during a fire hazard occurred in Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…Indeed, their empirical evidence is consistent with the findings of Abedin and Babar (2018). They uncover various categories of external social media participants and identify their corresponding motivation and levels of reliability for disaster management.…”
Section: Social Mediasupporting
confidence: 71%
See 3 more Smart Citations
“…Indeed, their empirical evidence is consistent with the findings of Abedin and Babar (2018). They uncover various categories of external social media participants and identify their corresponding motivation and levels of reliability for disaster management.…”
Section: Social Mediasupporting
confidence: 71%
“…Understanding these patterns is critical to unlock the SM potential in DM. The next three papers (Liu and Xu 2018;Abedin and Babar 2018;Ogie et al 2018) focus on SM and DM. The papers by Liu and Xu (2018) and by Abedin and Babar (2018) offer new theoretical insights and expose the limits of some existing IS theories.…”
Section: Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies in the information systems and electronic commerce literature have already reported the influence of various isolated technical factors such as technology use [10], data integration [4], and type of digital technologies [1], [4] as well as non-technical factors like digital leadership [5] and human resource management, and business process management [17] on digital transformation of organizations. The next objective of this editorial emphasizes the importance of digital strategy and organizational capabilities in successful digital transformation of organizations.…”
mentioning
confidence: 99%